Clinical-Laboratory Markers Of Progression Of Non-Alcoholic Fatty Liver Disease - Хamrayev Аbror Аsrorovich; Yuldasheva Dilnavoz Xasanovna; Zokirov Aziz Choriyevich (Genius Journals, 2021)
Aim of the research to determine the clinical and laboratory features of non-alcoholic fatty liver disease at the stage of fatty hepatosis and steatohepatitis.
Keywords: Laboratory; clinical